Problematika Guru Dalam Optimalisasi Media Pembelajaran IPAS Dikelas IV SDN 08 Lubuklinggau - Meilida Eka Sari; Lilis Setyawati; Peti Fitri Anggriani (Prodi PGMI Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2026)
Teacher problems are issues or problems experienced by teachers both when carrying out their duties at school and in educating, teaching, and guiding students while at school. This study aims to identify the problems teachers face in optimizing science learning media, how science learning media is used in fourth-grade students at SD Negeri 08 Lubuklinggau, and the supporting factors that influence these problems.This study employed a qualitative approach with a descriptive approach. Data collection techniques included observation, interviews, and documentation. Data analysis involved data reduction, data display, and verification. The subjects were the homeroom teacher, the principal, and fourth-grade students at SD Negeri 08 Lubuklinggau.The results indicate that teachers face problems in optimizing science learning media, indicating that their ability to utilize learning media is still inadequate, their creativity is insufficient to optimize media effectively, the media is still too boring, and they do not introduce new innovations in the learning process. The use of instructional media, however, was only used by a science teacher once. However, at that time, some students still struggled to understand what the teacher was conveying or teaching. Ultimately, the teacher never used instructional media again, always relying on printed textbooks and explaining the conclusions of the material in the textbook. Many factors also influenced the teacher's challenges, including the availability of resources in the form of printed textbooks, which are more practical because students have their own, comfortable and suitable classroom facilities, whiteboards in each classroom, and adequate teacher training. Efforts were made to plan, develop, and use instructional media. This was followed by an evaluation phase.